Phytochemical Methods Guide To Modern Techniques Of Plant Analysis - Harborne, J B (Springer P Ltd, 1998)
This book is a key tool in plant biochemistry, plant taxonomy where the analysis of organic plant components is key to their investigations.
Keywords: PHYTOCHEMISTRY; PLANT ANALYSIS; BIOORGANIC CHEMISTRY